Dimensionality and factor structure for the scale of teachers attitude toward inclusion - Jiar, Y. K. (Serials Publications, 2016)
The initial Scale of Teachers' Attitudes Toward Inclusion (STATIC) was developed to measure teachers' attitudes towards students with special needs in inclusive classroom. There were four subscales namely Advantages and Disadvantages (ADV), Professional Issues (PI), Philosophical Issues (PhI), and Logistical Concerns (LC) being identified by Cochran (1997) via factor analyses. The purpose of this study is to explore the cross-validating and reliability testing the scale among Malaysian teachers who are involved in Inclusive Education Programme. Measures of Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) conducted shown that STATIC (within Malaysian context) is a multi-dimensional scale with two factors structured: Advantages (AV) and Professional Issues (PI). Cronbach's Alpha reliability coefficient value was 0.73. Therefore, results indicated that the 8-item-STATIC can serve as a valid and reliable instrument for Malaysian teachers in Inclusive Education Programme.